Optimizing City Spatial Plans: Development Strategy Urban Sustainability in Medan - Muhammad Aris; Cut Nuraini (Yayasan Multidimensi Kreatif, 2024)
This research aims to investigate the optimization of urban spatial planning as a sustainable development strategy in the city of Medan. Medan, as one of the largest cities in Indonesia, faces various challenges in managing rapid urban growth. Using qualitative and quantitative approaches, this research analyzes current urban conditions, the sustainable development challenges faced, and strategies that can be adopted to achieve sustainable development goals. The research findings highlight the need for integration between spatial planning policies, environmental management, transportation and infrastructure in designing sustainable urban development plans. In addition, community participation and cross-sector collaboration are also needed to ensure broad acceptance of development plans. This research provides valuable insights for policy makers, stakeholders and academics in designing sustainable urban development strategies in Medan and other cities.